EFEKTIVITAS SISTEM INFORMASI AKUNTANSI DI BADAN KESATUAN BANGSA DAN POLITIK KOTA SEMARANG - Ulfa, Farizka Yunia; Hariani, Dyah (Journal of Public Policy and Management Review, 2016)
Accounting information system effectiveness in Badan Kesatuan Bangsa dan Politik Kota Semarang is effected by a obligation to be accountable and transparent of state’s finance by a financial statement that was made from acconting information system. The phenomena that affect the effectiveness of accounting information system were data security, time, accurancy, variation of output and relevancy. The affecting factor were human resources, time and completeness of data. The solutions that given are: (1) to increase the soft skill of human resources especially time discipline by giving a strict penalty to employee to discipline them, (2) to increase the ability of accounting information system to overcome system crash that can affected employee performance and (3) from the aspect of completeness of data, employees that are producing the finance data should be moved from manual system to accounting information system so that it will decrease the possibility of uncompleteness data by giving them a training.